Suspended Slot Membrane Waveguide Based on Germanium-on-Silicon-on-Insulator at λ = 4.23 µm for CO2 Monitoring - Muhammad A. Butt; Ryszard Piramidowicz (Micromachines)
In this work, we propose a novel suspended slot membrane waveguide (SSMW) utilizing a germanium-on-silicon-on-insulator (Ge-on-SOI) platform for carbon dioxide (CO2) gas-sensing applications. The design and analysis focus on the absorption line of CO2 in the mid-infrared region, specifically at a wavelength of 4.23 µm. The waveguide geometry has been precisely optimized to achieve a high evanescent field ratio (EFR) and minimize waveguide propagation losses. These optimizations significantly enhance the sensitivity of the waveguide, making it highly effective for evanescent field absorption-based gas sensing. Our optimized waveguide geometry demonstrates a notable EFR of 0.86, with a low propagation loss of just 1.07 dB/cm, and achieves a sensitivity as high as ~1.12 × 10−4 ppm−1 for SSMW lengths as short as 0.9 cm.